The Effects of an Experimental Intervention on Reading Decoding in the First Grade of San José Pinula, Guatemala - Flores Reyes, Mónica (2022)
This paper aims to explain the association between the development of reading skills in Spanish as native language with the teaching method and the academic and socio-demographic characteristics of first grade students from San José Pinula, Guatemala. This through a quasi-experimental design and a sample of 104 students, distributed in control and experimental groups. In 2016, the Reading Evaluation for Initial Grades (ELGI) develop by the Education Ministry of Guatemala was applied. The research was developed in two stages, in the first, the researchers characterized the methods implemented by first grade professors to teach reading and writing. During the second phase, the authors implemented the methodological intervention with didactic materials, methodological training, and support for teachers throughout the school year: experimental (comprehensive phonological) and control (syllabic). The results of the multiple linear regression model showed that the implementation of the method was significantly associated with the development of the following skills: phonological awareness, alphabetic principle, decoding and automation, while there were no differences in fluency between the experimental group and the learning group control. Likewise, the method contributed to explain the development of these skills in conjunction with the academic and sociodemographic characteristics of the students. To overcome the learning gap after the pandemic, the authors recommend strengthening teacher training in more effective methods, such as comprehensive phonology, for teaching reading through the design of didactic guides and workbooks for students that promote activities systems for learning these skills. The foregoing must be added to an intensive pedagogical strategy to reduce the initial reading delay and an incentive policy to ensure that the best teachers are assigned and remain in the first grade of primary school.